Kontribusi pendapatan usaha Ikan Bandeng di Desa Ulu Lalimbue, Kecamatan Kapoiala, Kabupaten Konawe - Namran, Usma; Nur, Muhammad; Sufa, Basri (Fakultas Pertanian Universitas Muhammadiyah kendari, 2024)
Ulu Lalimbue Village, Kapoiala District, Konawe Regency, Southeast Sulawesi Province, is known as a milkfish producer, where fish commodities are one of additional sources of income for farmers outside the main income of farmers. This study aims to determine the amount of income of milkfish farmers and find out how much the contribution of milkfish pond business income to farmer household income. Determination in this sampling uses the census sampling technique (saturated sampling). This study took respondents as many as 20 milkfish pond farmers. Primary data in this study were obtained using direct observation, interviews, and documentation. Secondary data are obtained from records and documentation from parties or agencies related to this study. The results of this study show that the average income of the milkfish pond business in Ulu Lalimbue Village, Kapoiala District, Konawe Regency is Rp. 6.999.813/production, and the average income of the main or outside the pond business is Rp. 24.549.800. The contribution of the milkfish farming business average 22,19% of the total household income of farmers. Keywords: Milkfish, Production Costs, Contribution, income